EIGHT CASES OF DEATH ASSOCIATED WITH FETAL FALCIPARUM MALARIA - Oña Gil, José (2015)
OBJETIVE: To determine the clinical characteristics of pregnant women with falciparum malaria and stillbirth. DESIGN: cross-sectional descriptive study. MATERIAL AND METHODS: All cases of pregnant women with falciparum malaria treated at the Hospital de Apoyo III of Sullana during 1998 and 1999. Of all these cases studied were identified who studied with fetal death and they were required characteristics clinics. All data were processed in Excel. RESULTS: Among the 88 cases of pregnant women with malaria caused by Plasmodium falciparum identified with thick film study, there were 8 cases of pregnant women with stillbirth were enrolled, representing a rate of 90.9 per 1,000 live births. Time of disease was mostly 6 or more days. Of the 8 cases, 6 received prior treatment, which were predominantly first-line drugs (chloroquine). The fetal death occurred predominantly during pregnancy, although two were given during labor. It was common fever, chills and malaise and all complications were detected, including kidney failure, neurological impairment and pulmonary edema. CONCLUSIONS: Among pregnant women who have falciparum malaria is common stillbirth; hence the need to strengthen malaria control programs.